2006
DOI: 10.1002/app.25457
|View full text |Cite
|
Sign up to set email alerts
|

Surface and pore structure modification of cellulose fibers through cellulase treatment

Abstract: The surface and pore structure of cellulose fibers have a significant impact on the properties and performance in applications. Cellulase enzymatic hydrolysis of cellulose fibers can result in changes to the surface and pore structure, thus providing a useful tool for fiber modification. This research characterizes these changes using various test methods such as fiber dimension, water retention value (WRV), hard-to-remove (HR) water content, freezing and nonfreezing bound water content, polymer adsorption, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…It has been reported that enzymatic hydrolysis of crystalline cellulose increases the roughness of the cellulose surface, and the structure becomes more receptive for protein adsorption. The surface area of pure cellulosic substance also increases due to enzymatic reaction (Park et al, 2007;Wang et al, 2005). The physical properties of the surface, however, affects only the mass transfer, a minor portion of the overall resistance, and its effect is shown at the initial phase the reaction.…”
Section: Effect Of Physical Properties On Ncc Hydrolysismentioning
confidence: 98%
“…It has been reported that enzymatic hydrolysis of crystalline cellulose increases the roughness of the cellulose surface, and the structure becomes more receptive for protein adsorption. The surface area of pure cellulosic substance also increases due to enzymatic reaction (Park et al, 2007;Wang et al, 2005). The physical properties of the surface, however, affects only the mass transfer, a minor portion of the overall resistance, and its effect is shown at the initial phase the reaction.…”
Section: Effect Of Physical Properties On Ncc Hydrolysismentioning
confidence: 98%
“…They speculated that these cavities were the result of initial dislocations, within which cellulases bound to and degraded amorphous and/or crystalline cellulose. Park et al (2007) showed that incubation of fully bleached Kraft pulp fibers with T. reesei cellulase resulted in significant fiber segmentation, i.e. ''cuts'' occur in the cross section, not the axial direction of the fibers.…”
Section: Hydrolysismentioning
confidence: 99%
“…The determination of the crystallinity index is highly dependent on the characterisation method [39]. It has been recognized that the actual values of the crystallinity differ according to the measurement principles and analysis techniques used, and that the highest crystallinity index is realized by the X-ray diffraction peak height method, and is bulk measurement performed in the dry state.…”
Section: Crystallinitymentioning
confidence: 99%
“…This was also investigated by scanning electron microscopy (SEM) and results showed a clear decrease in the length of cotton linters and a non-uniformity of particle size after several hours of enzymatic hydrolysis [29,35]. Using Fiber Quality Analyser Park et al [39] showed a clear decrease in particle size and other authors [3,37] correlated the particles size decrease to the increase in surface area.…”
Section: Introductionmentioning
confidence: 99%